The assessment of soil quality of various age of land reclamation after coal mining: a chronosequence study - A Noviyanto; P Purwanto; S Minardi; S Supriyadi (Journal of Degraded and Mining Lands Management, 2017)
The assessment of soil quality index is one of the parameters to evaluate the goal of land reclamation. The research has been done in the various age of soil of PT Adaro Indonesia and natural forest. The research used descriptive explorative method and open field survey. Purposive sampling was used to take the sample in research location that represented the condition of every location. Principal component analysis used to know the main indicator. The main indicator was based on Eigen value >1 and chosen by indicator correlation having the highest weight index. The main indicator chosen was called minimum data set. The result of the research showed that minimum data set consisted of pH, base saturation, bulk density, electrical conductivity, cation exchange capacity, available P, total N, and soil organic carbon. The main indicators contributing to soil quality index value were total N and cation exchange capacity. Variable linear analysis showed that the longer age of land reclamation was followed by the development of soil quality index. Soil quality index in 18 years old soil reclamation (0.651) was higher than that in natural forest (0.575). Soil quality index of > 0.5 is defined as sustainable reclamation.